EFEKTIVITAS PENERAPAN ASAS PRESUMPTION OF INNOCENCE OLEH PERS DALAM PEMBERITAAN TINDAK PIDANA MAKAR - Samaludin Samaludin; Nining Irianti (Jurnal Ilmu Hukum Kanturuna Wolio, 2022)
This study aims to determine the extent to which the effectiveness of the application of the principle of the Presumption Of Innocence by the Press in conductin a report, especially on treason crime. Primary data source research methods in the form of literature study, legislation and journals and other literature, secondary data sources in the form of interviews from research sources. Data collection method is a qualitative data collection method that focuses on the general principles underlying the manifestation of symptom units in human life, or the patterns analyzed are social phenomena by using the culture of the community concerned to obtain a picture of prevailing patterns. Method of presenting data obtained or data collected during the study in the form of primary data and secondary data were analyzed qualitatively then presented descriptively. Based on research and discussion of the main issues raised in this thesis, namely that the press or journalists must abide by the presumption of innocence in presenting news and information in accordance with applicable laws and regulations, obeying journalistic code of ethics so that violations do not occur and as law enforcement efforts carried out by the press. The press council as the agency that oversees the press must conduct more oversight of the media and the press in Indonesia.